2006
DOI: 10.1534/genetics.105.049353
|View full text |Cite
|
Sign up to set email alerts
|

Genomic Survey of Gene Expression Diversity inArabidopsis thaliana

Abstract: Differential gene expression controls variation in numerous plant traits, such as flowering time and plant/ pest interactions, but little is known about the genomic distribution of the determinants of transcript levels and their associated variation. Affymetrix ATH1 GeneChip microarrays representing 22,810 genes were used to survey the transcriptome of seven Arabidopsis thaliana accessions in the presence and absence of exogenously applied salicylic acid (SA). These accessions encompassed 80% of the moderate-t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

14
106
3

Year Published

2006
2006
2018
2018

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 107 publications
(123 citation statements)
references
References 43 publications
14
106
3
Order By: Relevance
“…This small degree of overlap was not surprising as calculations of gene expression levels average the hybridization intensities for all probes of a probe set and specifically eliminate the outlier probe values (http://www.affymetrix.com). Individual SFPs have only a small effect on quantifying gene expression levels (Kliebenstein et al 2006), and >95% of Arabidopsis genes with a SFP contain fewer than three SFPs per probe set (Borevitz et al 2003). Both the GEMs and SFP markers were randomly distributed throughout the genome with no evidence of clustering.…”
Section: Sfp Detection With Ril Datamentioning
confidence: 99%
See 1 more Smart Citation
“…This small degree of overlap was not surprising as calculations of gene expression levels average the hybridization intensities for all probes of a probe set and specifically eliminate the outlier probe values (http://www.affymetrix.com). Individual SFPs have only a small effect on quantifying gene expression levels (Kliebenstein et al 2006), and >95% of Arabidopsis genes with a SFP contain fewer than three SFPs per probe set (Borevitz et al 2003). Both the GEMs and SFP markers were randomly distributed throughout the genome with no evidence of clustering.…”
Section: Sfp Detection With Ril Datamentioning
confidence: 99%
“…RNA was extracted, labeled, and hybridized to Affymetrix ATH1 GeneChips representing 22,810 genes, as previously described (Kliebenstein et al 2006). GeneChips were scanned on an Affymetrix GeneArray Scanner using GCOS software (Affymetrix).…”
Section: Rna Isolation and Microarray Hybridizationmentioning
confidence: 99%
“…Recent studies of Arabidopsis populations have revealed considerable variation in both the genomic and the transcriptomic level (Kliebenstein et al, 2006;Clark et al, 2007;Kim et al, 2007). It is very unlikely that only one or a few genetic changes differentiate AZ and UT.…”
Section: Ecological and Evolutionary Significancementioning
confidence: 99%
“…ELPs in response to exogenously applied salicylic acid and jasmonic acid (JA) have been shown for many genes among different Arabidopsis accessions (Traw et al, 2003;Kliebenstein et al, 2006;van Leeuwen et al, 2007). In different populations, ELPs in particular genes have been shown to produce variation in pathogen resistance (Grant et al, 1995;Gassmann et al, 1999), flowering time (Johanson et al, 2000;Lempe et al, 2005;Werner et al, 2005), herbivore resistance, and secondary metabolite production (Kliebenstein et al, , 2002Lambrix et al, 2001).…”
mentioning
confidence: 99%
“…The generation of new pathways within species by evolution and selection requires the manipulation of genes to create new enzymes as well as new developmental structures to house these pathways via a variety of mechanisms [24][25][26]. An analysis of genetic variation within Arabidopsis showed that there was a high level of genetic diversity within the glucosinolate secondary metabolite pathway which arose within the Brassicales [27,28]. This secondary metabolite pathway diversity was also linked to elevated diversity in the genes of the sulfur associated pathways [27].…”
mentioning
confidence: 99%